PELAKSANAAN TUGAS SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN GELANDANGAN DAN PENGEMIS DI KOTA PEKANBARU - Roza Erdillah; Hendry Andry (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
General problem ofhomeless and beggras in fact closely related to the security problems that disrupt good order and discipline and keamanan in urban areas. With the expansions of the homeless and beggars will provide opportuneties for the emergance of unexpected disturbance of peace and order, which i turn woild disrupt the stability to be disrupted development and national ambitions can not be astablished. In this case civil service policy is most responsible agency because they were on duty apparatuses assits local government in maintaining the District Head and maintain public order and Security society, upholding the District Rules and Regulation of the District Head. Based on the homeless and beggars in the city of Pekanbaru, as well as know the Policy Unit blockers factor in regulating civil service homaless and beggars. The method used is descriptive, qualitative and quantitative; Samples that as descriptive data analysis, qualitative and quantitative. This study concluded that based on the results of research that has been done, then the concluded of researchers on the role of Civil Service Police Unit in the discipline vagrants and beggars in the city of Pekanbaru is “Good Enough”. Barriers found in this study is the absence of regulations governing theparticulars of vagrants and beggars, while the current police authority of the Civil Service in the city of Pekanbaru to crub vagrants and beggars who violate public onder just based on the Rules of Pekanbaru City Regionel Public Order so that it this makes the role of the Civil Service Pekanbaru City police are very limited. Also still weak coordination between the police civil service with the Departement of Social Pekanbaru is also a very in fluuetial factor in determining the role of the Civil Service Pekanbaru City police in maintaining public orde in the city of Pekanbaru.